2012
DOI: 10.1042/bj20111383
|View full text |Cite
|
Sign up to set email alerts
|

β2-Glycoprotein I inhibits endothelial cell migration through the nuclear factor κB signalling pathway and endothelial nitric oxide synthase activation

Abstract: β₂-GPI (β₂-glycoprotein I) is a plasma glycoprotein ascribed with an anti-angiogenic function; however, the biological role and molecular basis of its action in cell migration remain unknown. The aim of the present study was to assess the contribution of β₂-GPI to HAEC (human aortic endothelial cell) migration and the details of its underlying mechanism. Using wound healing and Boyden chamber assays, we found that β₂-GPI inhibited endothelial cell migration, which was restored by its neutralizing antibody. NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…Results showed a statistical significance using the concentration of 100 μmmol/L beta2-GPI or reduced beta2-GPI. Synthesizes related references [13,14,18,19] and our preliminary experiment, the concentration of 100 μmmol/L was selected for the mechanism study.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed a statistical significance using the concentration of 100 μmmol/L beta2-GPI or reduced beta2-GPI. Synthesizes related references [13,14,18,19] and our preliminary experiment, the concentration of 100 μmmol/L was selected for the mechanism study.…”
Section: Discussionmentioning
confidence: 99%
“…30,32 SAA is a relatively small protein of ~12 kDa 33 with ~80% alpha helical conformation. 34 β2GPI, also known as apolipoprotein H, 35 is a multifunctional 53 kDa glycosylated plasma protein 36 with physiological values of 20-300 mg/L. 37 The protein consists of 326 amino acids folded into five domains, where the fifth domain is positively charged, with a lysine-rich region 281 CKNKEKKC, 288 a hydrophobic loop 313 LAFW, 316 and extended C-terminal domain, that enable binding to negatively charged phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] We showed previously that purified β 2 -GPI inhibits cell migration, proliferation, and angiogenesis in human aortic endothelial cells. [9][10][11] However, the role of natural β 2 -GPI in tumor development remains unknown. The present study showed that β 2 -GPI is a negative regulator of cell migration, proliferation, and invasion in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that β 2 -GPI plays an essential role in the suppression of vascular endothelial cell growth, cell migration, and angiogenesis under the regulation of nuclear factor-kappa B (NF-кB) signaling and vascular endothelial growth factor (VEGF)-mediated phosphorylation of VEGFR2, ERK1/2 and Akt pathways. [9][10][11] It is well established that abnormal cell migration and proliferation are closely related to carcinogenesis. [12][13][14][15] Furthermore, many studies have reported that inhibition of cell migration decreases tumor growth in multiple cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation